"God, die Allerhoogste, woon nie in mensgemaakte konstruksies nie" - Dreyer, T. F. J. (HTS teologiese studies, 2004)
“God, Almighty, does not live in human made constructs”This article is a homiletic reflection on the words of Stephen in Acts 7:48f that “the most High dwelled not in temples made with hands; as said the prophet, ‘Heaven is my throne, and earth is my footstool: what house will ye build me? said the Lord: or what is the place of my rest?’” The explication and application of these words are theologically contextualised with respect to current debates among theologians in the Nederduitsch Hervormde Kerk. The perspective represented in this reflection is based on the belief that faith affirmations had developed from a fundamental religious experience. When shared by others in a particular time and cultural context, the expressed faith experience became articulated in metaphorical language. From here on it could be transformed into a dogmatic creed, distanced from its origins. Putting one’s trust in dogma as metaphorical language without participation in the fundamental religious experience expressed by creedal language, amounts to confining God to human made constructs. The article focuses on several faith affirmations, such as God’s creation, Jesus’ virginal conception and his resurrection, and the expiation of sins.